(untitled) (Journal of Environmental Science and Natural Resources, 2017)
Soils of the Low Ganges River Floodplain encroaching Faridpur district of Bangladesh have immense contribution to crop production, while little information available focusing the spatial variability of trace elements in the area. Therefore, the study was conducted to quantify the trace elements collecting a total of 122 representative soil samples from rice fields of Faridpur district. Soil samples were analyzed and found that Cu, Fe, Mn, Zn and B were ranged from 0.80-6.80, 24295, 10129, 0.122.20 and 0.5-9.05 ppm, respectively. The pollution indexes are noteworthy features which revealed that only Mn may exhibit a risk for environmental pollution. The concentrations of trace elements, pH and organic carbon in soils displayed a significant spatial diversity because of anthropogenic and geogenic contribution. The distribution maps of soil pH, organic carbon and trace elements might be useful to farmers, researchers and planners in designing and planning agricultural programs in the study area. J. Environ. Sci. & Natural Resources, 9(2): 71-78 2016